Analysis Energy Losses in the Distribution Network System at PT. PLN (Persero) ULP Indramayu (Case Study of Loh Beneficial Feeders) - Soleh, Muhamad; Taryo, Taryo; Kurniawan, Aditya (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2023)
At PT PLN (Persero) Indramayu Customer Service Unit, it was recorded that electrical energy supplied from the substation at PT PLN (Persero) Indramayu Area in 2019 was 347,133,287.9 ​​kWh, while the energy sold was 312,676,929 kWh and the amount of energy losses of 34,456,358.9 kWh.[5] The difference in the amount is due to energy losses or losses. Energy losses are the amount of energy lost in the energy flow process from the substation or distribution substation to the consumer. This is caused by two factors, namely technical and non-technical factors. Technical factors caused by distribution network problems. The study carried out was a study of energy loss on feeders, namely the Lohbene feeder, this name is an aid to the name of the feeder from ULP Indramayu. The object specification data for this study were obtained based on data from ULP Indramayu and the Indramayu Service Unit. After conducting the research, it can be concluded that the technical losses in the Lohben feeder are 1120.94 kW, while the non-technical losses are 189.96 kW. The annual losses in the Lohben feeder are 8,315,678.42 kWh. reduced to 482.69kW, which was previously 875.486kW. After technical improvements, losses decreased to 406.430 kW per month